Construction of engineered Saccharomyces cerevisiae strain to improve that whole-cell biocatalytic production of melibiose from raffinose. (1st March 2017) - Zhou, Yingbiao; Zhu, Yueming; Men, Yan; Dong, Caixia; Sun, Yuanxia; Zhang, Juankun
Abstract: There are excessive by-products in the biocatalysis process of this whole-cell biocatalytic production of melibiose from raffinose with current Saccharomyces cerevisiae strains. To solve this problem, we constructed engineered strains based on a liquor yeast ( S . cerevisiae ) via gene deletion ( mel1 gene), heterologous integration ( fsy1 or/and ffzi1 gene from Candida magnoliae ), and gene overexpression ( gcr1 gene). Functional verification showed that deletion of the mel1 gene led to elimination of the reactions catalyzed by α-galactosidase, as well as elimination of the degradation of melibiose and the formation of galactose by-product. Insertion of the fsy1 or/and ffzi1 gene and overexpression of the gcr1 gene could contribute to fructose transport for enhancing the biopurification rate of the fructose by-product. Compared with the wild-type strain, the optimal engineered strain of MP8 (Δ mel1 :: fsy1 cm :: ffzi1 cm :: gcr1 sc ) had improved about 30% on yield, 31% on productivity, and 36% on purity of the melibiose product.